Catatonia Psychopathology and Phenomenology in a Large Dataset - Dawkins, Eleanor; Cruden-Smith, Leola; Carter, Ben; Amad, Ali; Zandi, Michael S.; Lewis, Glyn; David, Anthony S.; Rogers, Jonathan P. (Frontiers in Psychiatry, 2022)
Background The external clinical manifestations (psychopathology) and internal subjective experience (phenomenology) of catatonia are of clinical importance but have received little attention. This study aimed to use a large dataset to describe the clinical signs of catatonia; to assess whether these signs are associated with underlying diagnosis and prognosis; and to describe the phenomenology of catatonia, particularly with reference to fear. Methods A retrospective descriptive cross-sectional study was conducted using the electronic healthcare records of a large secondary mental health trust in London, United Kingdom. Patients with catatonia were identified in a previous study by screening records using natural language processing followed by manual validation. The presence of items of the Bush-Francis Catatonia Screening Instrument was coded by the investigators. The presence of psychomotor alternation was assessed by examining the frequency of stupor and excitement in the same episode. A cluster analysis and principal component analysis were conducted on catatonic signs. Principal components were tested for their associations with demographic and clinical variables. Where text was available on the phenomenology of catatonia, this was coded by two authors in an iterative process to develop a classification of the subjective experience of catatonia. Results Searching healthcare records provided 1,456 validated diagnoses of catatonia across a wide range of demographic groups, diagnoses and treatment settings. The median number of catatonic signs was 3 (IQR 2–5) and the most commonly reported signs were mutism, immobility/stupor and withdrawal. Stupor was present in 925 patients, of whom 105 (11.4%) also exhibited excitement. Out of 196 patients with excitement, 105 (53.6%) also had immobility/stupor. Cluster analysis produced two clusters consisting of negative and positive clinical features. From principal component analysis, three components were derived, which may be termed parakinetic, hypokinetic and withdrawal. The parakinetic component was associated with women, neurodevelopmental disorders and longer admission duration; the hypokinetic component was associated with catatonia relapse; the withdrawal component was associated with men and mood disorders. 68 patients had phenomenological data, including 49 contemporaneous and 24 retrospective accounts. 35% of these expressed fear, but a majority (72%) gave a meaningful narrative explanation for the catatonia, which consisted of hallucinations, delusions of several different types and apparently non-psychotic rationales. Conclusion The clinical signs of catatonia can be considered as parakinetic, hypokinetic and withdrawal components. These components are associated with diagnostic and prognostic variables. Fear appears in a large minority of patients with catatonia, but narrative explanations are varied and possibly more common.